Existence of two sets of kinetic parameters in the correlation of the hydrogen electrode reaction - Gennero, Maria Rosa (2000)
It has been demonstrated that the dependence of the current density on overpotential for the hydrogen electrode reaction described through the Volmer-Heyrovsky-Tafel mechanism can be correlated by two different sets of the kinetic parameters. Such sets lead to two different dependences of the surface coverage on overpotential, while a unique dependence of the corresponding pseudocapacitance of adsorption is obtained. The expressions that relate both sets of kinetic parameters have been established and analyzed for the simultaneous occurrence of the three steps and for the different kinetic routes.